P PERBANDINGAN AKTIVITAS ANTI BAKTERI SABUN PADAT TRANSPARAN MINYAK ATSIRI SEREH WANGI (Cymbopogon citrates (DC.) Stapf) TERHADAP BAKTERI Staphylococcus aureus Dan Escherycia coli - Betna Dewi (Oceana Biomedicina Journal, 2023)
Citronella (Cymbopogon citrates (DC.) Stapf) is one type of plant that has the potential to produce essential oils. In general, the content of citronella scented lemongrass can inhibit the growth of Gram positive and Gram negative bacteria. The research process was carried out using the disc diffusion method to obtain results from the comparison of the activity of antibacterial solid soap of citronella essential oil (Cymbopogon citrates (DC.) Stapf) against Stapylococcus aureus and Escherycia coli bacteria, with different soap concentrations, namely F0 transparent solid soap without substances. active citronella essential oil, F1 transparent solid soap with 1% citronella oil, F2 transparent solid soap with 1.5% citronella essential oil, F3 transparent solid soap with 2% citronella essential oil. The test method used is by diffusion discs tested for antibacterial activity of staphylococcus aureus and escherycia coli on citronella transparent solid soap. The results that can be tested for antibacterial activity are Staphylococcus aureus which has a very strong average zone of inhibition, while Escherycia coli has a strong average zone of inhibition as an anti-bacterial.